Optimising the Role of Madrasah Supervisors in Implementing Merdeka Belajar Policy to Improve Academic Quality - Khoiruddin, Khoiruddin; Nasution, Wahyudin Nur; Syukri, Makmur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyse the roles and functions of supervisors in implementing the Merdeka Belajar policy at Islamic senior high schools (MAN) in Aceh Tamiang to improve students’ academic quality. The research focuses on four key supervisory functions: coaching, monitoring, evaluation, and training. Using a qualitative phenomenological approach, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that supervisory efforts—such as guidance to teachers, training in innovative methods, routine monitoring, and data-driven evaluations—have significantly enhanced teaching quality and student motivation. Key supporting factors included principal support, teacher collaboration, and adequate facilities, while limitations such as time constraints and resistance from some teachers hindered effectiveness. The study underscores that the success of Merdeka Belajar implementation relies on active and collaborative engagement among supervisors, teachers, and school leadership. Practically, this research highlights the need to empower school supervisors as strategic partners in curriculum reform. Education stakeholders should provide structured support, adequate resources, and professional development opportunities for supervisors. Future research should expand to include various Islamic education institutions across different regions to account for contextual diversity. Longitudinal studies are also recommended to examine the sustained impact of supervisory practices on student outcomes and instructional transformation under the Merdeka Belajar framework.